S2e-Leitlinie der Deutschen Urologen: Konservative und medikamentöse Therapie des benignen Prostatasyndroms = S2e guideline of the German urologists : conservative and pharmacologic treatment of benign prostatic hyperplasia - Höfner, Klaus; Michel, Maurice Stephan (Der Urologe, 2016)
This report summarizes the relevant aspects of the S2e guideline of the German Urologists for the conservative and pharmacological treatment of lower urinary tract symptoms due to benign prostatic hyperplasia. Recommendations are given regarding watchful waiting, behavioral therapy, phytotherapy and pharmacological mono- and combination therapy. The influence of the different therapeutic options on bladder outlet obstruction (BOO) is described in detail.
Gesehen am 29.01.2019
Online publiziert: 1. November 2015